Islamic Architecture and Contemporary Politics: Mosques in Constantine (Algeria) and Casablanca (Morocco) - Мaciel, Lev (Actual Problems of Theory and History of Art, 2017)
This article deals with a topical theme — the architecture of the contemporary mosque. There are only a few monographs on the subject, and even fewer case studies which analyze the architecture of individual buildings in their political context. This article is dedicated to the mosques of Abd al-Qadir in Constantine,Algeria (1972–1994, Ismail Hussein Mohammed) and Hassan II in Casablanca, Morocco (1987–1993, Michel Pinseau) and presents the results of onsite research in 2014–2016. The first of the above-mentioned mosques has not been studied before, and therefore much more attention is paid to it. The author argues that both mosques combine traditional decoration with contemporary spatial solutions, for example the bold diagonal setting of the Casablanca’s minaret. The decoration of this mosque is focused solely on national heritage, but at the same time it is supplemented with modern details and materials. All this should emphasize both the traditionalism and the modernity of Hasan II’s monarchy, as well as include Casablancain the orbit of the traditional Islam controlled by the king. The creators of the mosque in Constantine оpenly abandoned modernization attempts and emphasized the exact reproduction of the iconic forms of the architecture of Maghreb and al-Andalus. These forms should underline the status of the first Islamic university in socialist Algeria of the 1970s as the new cultural center of the entire Western Islamic world.
Keywords: Islamic art; mosque; contemporary architecture; Revivalism; Modernism; Postmodernism; Algeria; Morocco; Casablanca; Constantine